PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN (Studi pada Guru - Guru SD di UPT Disdikpora Kecamatan Gringsing Kabupaten Batang) - Kisbandiyah, Sri; Fauzan, Mohammad (Students Journal of Economic and Management, 2012)
This study aims to analize the influence of commitment and competence on teacher performanceÂ moderated by leadership in elementary school teachers with the status of Civil Servants (PNS) at UPT Disdikpora Gringsing Regency, Batang District. Population in this research are elementary school teachers civil Servants amounted to 178 people. The number of samples in this study were 124 people. Measurement of responses to questionnaires using a likert scale of 7 (seven) alternative answer. Testing instrument using validity and reliability, are testing a model using the coefficient of determination and the F test (Goodness of Fit). Testing hypothesesÂ in this study using regression quasy interactions with significance level (Î±) 5%.The results showed 43,5% of the change in teacher performance variable can be explained by the influence of commitment, competence, leadership, commitment and leadership interaction, and competence and leadership interaction, was 56,5% explained outside the model. The results of hypotheses testing obtained the results that commitment positively and significance effect of the teacher performance, competence positively and significance effect of the teacher performance, leadership unsignificance effect of the teacher performance, leadership weaknessthen the influence commitment on teacher performance, and leadership weaknessthen the influence competence on teacher performance. Keywords: commitment, competence, leadership, teacher performance.